Models of start-up thinking and action theoretical, empirical and pedagogical approaches - Katz, Jerome A.; Corbett, Andrew C. (Bingley, U.K. : Emerald, 2016)
Volume 18 will focus on approaches to thinking about and creating the start-up. Both theoretical and empirical manuscripts that consider all aspects of start-up planning, thinking and action will be considered. We also encourage practice-based research and manuscripts that explore cutting-edge pedagogical approaches. The papers in Advances reflect many state-of-the-art topics and approaches, and are written by leading researches in the field, making each volume an important source of information for virtually all entrepreneurship researchers. One of the distinctive competences of research volumes such as Advances is that the chapters can be published without page restrictions allowing for greater detail in the background, development, and implementation of ideas than is possible in journal articles. This provides authors with the opportunity to fully express their key ideas, provide much more complete support, and include relevant multi-page appendices. In effect, the Advances series provides authors the opportunity to publish an "article of record" of their major theoretical or empirical ideas, and see it disseminated to a wide audience.
Towards a design science of entrepreneurship / Dimo Dimov -- Sociocultural context, entrepreneur types, mindsets and entrepreneurial action in Tiradentes, Brazil / Reed Nelson, Anderson Santana, Matthew Wood -- New venture planning and lean start-up activities: a longitudinal empirical study of entrepreneurial success, founder preferences and venture context / Benson Honig, Christian Hopp -- A design thinking-based conceptualization of the "how" and "what" of nascent social venture development / Aparna Katre -- The evolution of business plans in international business plan competitions / Charles Hofer -- An exploration of the phenomenon of business planning in nascent and young firms / Christopher Garonne, Per Davidsson -- How should entrepreneurship be taught to students with diverse experience? A set of conceptual models of entrepreneurship education / Zhaocheng (Elly) Zeng, Benson Honig.
Includes bibliographical references.
Print version record
Keywords: Business & Economics -- Entrepreneurship; Entrepreneurship; Entrepreneurship; New business enterprises; Business planning